Design of Pattern Reconfigurable Patch Antenna Array Based on Reflective Phase-Shifter - Yuqiu Shang; Qingsheng Zeng; Wanzhao Cui; Xinwei Wang; Gengqi Zheng (International Journal of Antennas and Propagation)
A circularly polarized (CP) broadside antenna array with a continuously adjustable beam is proposed and implemented. First, a reflection phase shifter with varactor diodes loaded on two output terminals of a branch directional coupler is realized. By controlling the voltage across both ends of the varactor diodes in the terminal load circuit, the reactance of the load is changed, allowing control of port phase shift. Following that, the microstrip patch antenna array is combined with the reflection phase shifter to achieve the pattern reconstruction for the array. For verification, a prototype of the designed pattern reconfigurable antenna (PRA) is fabricated and measured. The measurement results indicate that the beam direction of the antenna can be continuously adjusted with a change in the voltage across the varactor diodes. The maximum beam direction of the antenna reaches ±21° when the biggest DC bias voltage across the varactor diode is chosen as 15 V. Besides, the antenna shows good CP performance in different beam directions.